Perception of small- and medium-sized enterprises in Klang Valley, Malaysia towards profit and loss sharing mode of financing - Ab. Manan, Siti Khadijah; Abdullah, Moha Asri (Faculty of Economics and Administration, University of Malaya, 2012)
Equity financing on the basis of profit and loss sharing (PLS) had long been proposed by Muslim scholars to be the prevalent method of funding to businesses. This is so because scholars believe that this particular funding method is able to meet the true spirit of equitable distribution of income and wealth, hence materialising the goals of the shariah (maqasid al-shariah) in the economy. In addition, they viewed that a balanced proportion of equity and debt in a firm's financial structure would be able to yield a handsome return as the mode promotes participation and hard work while at the same time motivates business expansion and growth. Nevertheless, theoretical perceptions of the scholars on the mode would be less meaningful without ground support from businesses. This study therefore examines the perception of entrepreneurs towards PLS-equity financing. The small and medium-sized enterprises (SMEs) are chosen as samples of the study as these enterprises constitute the majority of business establishments in Malaysia. The study found a favourable finding in support of the scholars' view. The study proposes that PLS equity financing should be given premier attention by the respective bodies and agencies as current practices seldom offer this mode to businesses particularly smaller enterprises.